2022
DOI: 10.1177/10600280221077383
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Intrapleural Tissue Plasminogen Activator With or Without Dornase Alfa for the Treatment of Traumatic Retained Hemothorax: A 6-Year Experience

Abstract: Background: Intrapleural fibrinolytic instillation is second-line treatment for retained hemothorax. Dornase alfa (DNase) has demonstrated efficacy in parapneumonic effusion, but the lack of deoxyribonucleoproteins limits direct extrapolation to traumatic retained hemothorax treatment. Objective: This study evaluated the effectiveness of intrapleural tissue plasminogen activator (tPA) with and without DNase in the treatment of retained traumatic hemothorax. Methods: This retrospective cohort study included pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…While the use of IPFT is inherently appealing as a pharmacologic alternative to surgery, the approach is disadvantaged by the paucity of literature defining the optimal fibrinolytic agents to be used for RH, their dosing, and their schedules of administration, as is the case in empyema [ 19 , 20 ]. While understudied, one report suggested that the addition of DNase to tPA did not improve the outcomes of RH [ 21 ]. Whether the same forms of IPFT should be used for cases of RH as for empyema remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While the use of IPFT is inherently appealing as a pharmacologic alternative to surgery, the approach is disadvantaged by the paucity of literature defining the optimal fibrinolytic agents to be used for RH, their dosing, and their schedules of administration, as is the case in empyema [ 19 , 20 ]. While understudied, one report suggested that the addition of DNase to tPA did not improve the outcomes of RH [ 21 ]. Whether the same forms of IPFT should be used for cases of RH as for empyema remains unclear.…”
Section: Introductionmentioning
confidence: 99%